Income Analysis of Culinary Vendors at Tahoku Port, Hila Village, Leihitu District - Lamidin, Santi; Louhenapessy, William George; Sinay, Fransisca Riconita (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2022)
Tahoku Harbor is a Speed Boad crossing from Seram Island, Kelang Island and Manipa Island. At Tahoku Harbor, Hila Village, there are several kinds of culinary traders, there are green banana Culinary with a selling price of IDR 10,000 per bowl, Red Porridge with a selling price of IDR 5000 per glass, Yellow Rice with a selling price of IDR 10,000 per plate, Lapis Cake with a selling price Rp. 1,500 per piece, and fried food with a selling price of Rp. 1000 per piece. In this regard, this study was conducted to determine the level of income of culinary traders at Tahoku Port, Hila Village, Leihitu District. This type of research uses a qualitative method approach. The research informants are culinary traders at Tahoku Harbor, Hila Village, Leihitu District. Data can be obtained from observation, interviews and documentation. The data is then processed using the formula: total revenue divided by total cost, equal to revenue = TR- TC. The results of this study indicate that the income of culinary traders in Tahuko Harbor, Hila Village, Leihitu District is profitabel, so the business feasibility or R/C of culinary traders is 1.66 (feasible because the R/C is more than 1).